(untitled) (Sains Humanika, 2024)
The aim of doing this systematic review is to fill up the gap on the benefits, challenges, and impacts of flipped classrooms in English language instruction and learning. The research incorporates data from 36 empirical studies that were published between 2017 and 2023. Examining peer-reviewed literature from databases including Web of Science, ERIC, and Scholar Google, the review’s content analysis shows the finding are: Flipped classrooms have a positive impact on (1) student learning outcomes, which increased students’ academic achievement; (2) students’ motivation to learn and classroom engagement; (3) enhances social interaction skills and independent learning through group activities. The challenges include that: (1) Some students lack motivation; therefore, they skip watching lectures and materials on video outside of the classroom; (2) there are Issues related to technology, include unreliable internet connections and insufficient technical assistance and so on will set back the outcome. Despite the potential of the flipped classroom model to promote the effectiveness of English language learning, in order to fully realize this potential, improved technological infrastructure, professional development opportunities for teachers, and the cultivation of students’ self-directed learning skills are required to address the pedagogical and technological obstacles that arise during implementation. Future studies should concentrate on standardized assessment techniques, cross-cultural and educational environment comparisons, and long-term learning results.